Ecocritical Analysis of Natural Resource Exploitation in Jesyca Tina's Short Story Bumi Tak Seindah Dulu - Hasibuan, Debby Melviana; Juli Anjani; Muhammad Kemal Habib; Purwarno, Purwarno (ITScience (Information Technology and Science), 2024)
The study meticulously examines the pervasive theme of nature exploitation through an in-depth analysis of Jesyca Tina's evocative short story, Bumi Tak Seindah Dulu. By focusing on the adverse effects stemming from humanity's excessive exploitation of natural resources, such as environmental degradation, disasters, and ecosystem transformations, the research aims to provide profound insights into the intricate dynamics between humans and their natural surroundings as depicted in the short story. Through a carefully designed descriptive qualitative research methodology, the study meticulously gathers primary data directly from the narrative canvas of the short story, allowing for a comprehensive exploration of the themes and motifs therein. By grounding its analysis in the principles of eco-criticism, the research illuminates the complex interplay between human actions and environmental consequences, underscoring the urgent need for conscientious and sustainable practices. Moreover, the study emphasizes the narrative's pivotal role in fostering environmental consciousness and advocating for responsible stewardship of the planet. By shedding light on the intersections of literature, ecology, and ethical responsibility, the research serves as a compelling call to action for a paradigm shift towards more harmonious and sustainable coexistence with the natural world. Through its nuanced examination of these themes, the study seeks to inspire readers to reevaluate their relationship with the environment and embrace a more environmentally-conscious lifestyle.